Transcription factor DDIT3 is a potential driver in pancreatic cancer: DDIT3 is highly expressed in pancreatic cancer - Ju, Guoyuan; Gui, Bo; Chen, Yufeng; Chang, Xinxia; Feng, Zhenqing; Liu, Fangzhou; Zhang, Xiao (Cellular and Molecular Biology, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal and aggressive tumor that affects the digestive tract, leading to high mortality and poor survival rates. The purpose of the present study was to evaluate the expression levels of DNA damage-inducible transcript 3 (DDIT3) in pancreatic cancer and to investigate its effects in in vitro and in vivo experiments. Bioinformatics analysis indicated that DDIT3 expression was higher in pancreatic cancer tumor tissues and associated with a poor prognosis. Positive or strong positive DDIT3 expression was observed in PDAC, and no or weak expression was observed in normal pancreatic tissues. It was also highly expressed in PDAC cells, while being expressed at lower levels in normal pancreatic ductal epithelial cells. Transfection of short hairpin RNA targeting the DDIT3 gene reduced the proliferation, migration and invasion of PANC-1 cells. In vivo, in an in situ implantation tumor model with Pan02 cells, the size and weight of the tumors were reduced in the DDIT3 knockdown Pan02 cell-implanted group. These data suggested that DDIT3 represents a novel predictive biomarker for the potential treatment of patients presenting with PDAC.